Adenovirus prevents dsRNA formation by promoting efficient splicing of viral RNA. Issue 3 (21st October 2021) - Price, Alexander M; Steinbock, Robert T; Di, Chao; Hayer, Katharina E; Li, Yize; Herrmann, Christin; Parenti, Nicholas A; Whelan, Jillian N; Weiss, Susan R; Weitzman, Matthew D
Abstract: Eukaryotic cells recognize intracellular pathogens through pattern recognition receptors, including sensors of aberrant nucleic acid structures. Sensors of double-stranded RNA (dsRNA) are known to detect replication intermediates of RNA viruses. It has long been suggested that annealing of mRNA from symmetrical transcription of both top and bottom strands of DNA virus genomes can produce dsRNA during infection. Supporting this hypothesis, nearly all DNA viruses encode inhibitors of dsRNA-recognition pathways. However, direct evidence that DNA viruses produce dsRNA is lacking. Contrary to dogma, we show that the nuclear-replicating DNA virus adenovirus (AdV) does not produce detectable levels of dsRNA during infection. In contrast, abundant dsRNA is detected within the nucleus of cells infected with AdV mutants defective for viral RNA processing. In the presence of nuclear dsRNA, the cytoplasmic dsRNA sensor PKR is relocalized and activated within the nucleus. Accumulation of viral dsRNA occurs in the late phase of infection, when unspliced viral transcripts form intron/exon base pairs between top and bottom strand transcripts. We propose that DNA viruses actively limit dsRNA formation by promoting efficient splicing and mRNA processing, thus avoiding detection and restriction by host innate immune sensors of pathogenic nucleic acids. Graphical Abstract: